Exposure to particulate matter (PM10) in indoor air and lung function test among dental laboratory technologists and administration workers in Kota Bharu - Saidi, Nur Diyanah (Pusat Pengajian Sains Kesihatan, 2014)
Particulate matter (PM) is the substance that could affect the air quality as well as the health of surrounding people. This cross-sectional comparative study aimed to prove there is a significant relationship between exposure to PM10) lung function capability and respiratory symptoms among dental laboratory technologists and administration workers using consecutive sampling method. Sixty subjects were recruited from one private dental clinic, eight public dental clinic and one dental administration office in Kota Bharu. Forty subjects were dental technologists and twenty subjects were dental administration workers. Self-constructed questionnaire was used to gather data on socio-demographic, work characteristics and respiratory symptoms among subjects. Area and personal monitoring were conducted to measure PM10 concentrations. For personal PM10 exposure, TSI SidePak AM510 Personal Aerosol Monitor was attached to the worker for eight hours within breathing zone by clipping flexible suction tubing on the lapel and the pump was worn on a belt. The median of average exposure to PM10 recorded in dental technologists group is significantly higher 0.09 (IQR 0.07-0.13) pg/m3 compared to the dental administration workers group 0.02 (IQR 0.02) pg/m3 (p<0.05). COSMED Pony FX Desktop Spirometer was used in lung function test (LFT) which performed three times for each subject and the best result was selected. The LFT gave no significant difference between these two groups. Presence of respiratory symptoms depend on the duration of exposure, age and sensitivity of the exposed person. PM readings for both area and personal monitoring exceeded the PEL. Only wheezing (p=0.038) and severe cough (p=0.005) were significantly associated with average PM10 exposure. In conclusion, there was no significant relationship between exposure to PM10 with LFT. The management have to ensure the prevention and control measures are efficiently implemented and give training to the exposed population.